Management of pediatric penile keloid - Yong, Michael; Afshar, Kourosh; MacNeily, Andrew; Arneja, Jugpal S. (Canadian Urological Association Journal, 2013)
Keloids are abnormal scar tissue growths that extend beyond the original area of injury, occasionally occurring post-surgery. Risk factors for keloids include skin trauma, infection, prolonged wound healing and individuals of certain ethnicities. Keloid formation on the penis, however, is a rare occurrence even among circumcised males, and can produce both aesthetic and functional complications. We document the tenth patient in the literature, to our knowledge, to present with a keloid of the penis.